How harassment is depriving universities of talent: a national survey of STEM academics in the UK - Litzellachner, Lukas F.; Barnett, Julie; Yeomans, Lucy; Blackwood, Leda (Frontiers in Psychology, 2024)
Introduction Despite efforts to increase girls’ interest in subjects related to science, technology, engineering, and mathematics (STEM) careers, there remains a large gender gap in STEM academic faculty. Methods We conducted a national survey comprising 732 early career and senior academics from 40 universities in the UK to investigate the role of pull (receiving career advancement opportunities) and push (experiencing harassment) factors in shaping people’s intentions to stay in STEM academia, and the mediating role of perceived workplace climate, academic identification, and beliefs about the ability to succeed (job-related self-efficacy). Results Our findings show the differential effect of harassment experiences for women, relative to men. Women experienced more harassment than men, which contributes to their higher intentions to leave academia through enhancing perceptions of a negative workplace climate (i.e., a less collaborative, fair, and inclusive climate) and lower job-related identification (i.e., believing in their ability to succeed as researchers). While receiving opportunities also related to intentions of leaving academia, we did not observe a gender difference in this factor. Discussion The result of our analysis underlines the critical importance of preventing and addressing harassment in academic institutions for the retention of female academic talent.